Epigeous macrofungi of the Parque de Natureza de Noudar in Alentejo (Portugal) - Louro, R; Calado, M; Pinto, B; Santos-Silva, C (Mycotaxon, 2009)
This inventory represents the first list of the epigeous macrofungi collected in Parque de Natureza de Noudar (Barrancos, Alentejo, Portugal). Throughout 3 years 162 taxa were registered, from which 8 are new species for Portugal and 77 for Alentejo. Some of them are considered rare species whereas others have been suggested to acquire a conservation status.
Keywords: fungi; Holm oak; iberian peninsula; Mediterranean ecosystem; sporocarps

Epigeous macrofungi of the Parque de Natureza de Noudar in Alentejo (Portugal) - Louro, R.; Calado, M.; Pinto, B.; Santos-Silva, C. (Mycotaxon, 2009)
This inventory represents the first list of the epigeous macrofungi collected in Parque de Natureza de Noudar (Barrancos, Alentejo, Portugal). Throughout 3 years 162 taxa were registered, from which 8 are new species for Portugal and 77 for Alentejo. Some of them are considered rare species whereas others have been suggested to acquire a conservation status.
Keywords: fungi; Holm oak; iberian peninsula; Mediterranean ecosystem; sporocarps

Diversidad ectomicorrícica en una formación natural de carrasca (Quercus ilex L. subsp. ballota (Desf.) Samp.) - Clavería, Vanessa; De Miguel, Ana Mª (IV Congreso Forestal Español, 2005)
The aims of this study are to characterize the ectomycorrhizal community of a mature and well preserved evergreen oak forest (Quercus ilex L. subsp. ballota (Desf.) Samp.) and to relate the above- and below-ground species diversity. The study area is the Nature Reserve of Monte del Conde, which has been proposed to be included in the Sites for Community Importance (SCI) and for Special Areas of Conservation (SAC) for the European Community. In autumn 2003, in an area of 225 m2, 374 sporocarps belonging to 52 taxa were collected. Clavulina cinerea (Fr.) Schroet., Entoloma rhodopolium (Fr.) Kumm. and Tricholoma scalpturatum (Fr.) Quél. were the dominant species. Belowground, morphological and anatomical analyses of ectomycorrhizal root tips were performed, yielding a total of 41 types. Cenococcum geophilum Fr. and thelephoroid fungi were dominant species on the root system. The preliminary results show that the sporocarps survey does not reflect the real ectomycorrhizal community diversity. Therefore, it is important to sample both sporocarps and root tips to achieve an accurate estimate of the ectomycorrhizal fungal community in forest ecosystems.
Keywords: Ectomycorrhizae; ectomycorrhizal fungi; Quercus ilex; sporocarps

Diversidad ectomicorrícica en una formación natural de carrasca (Quercus ilex L. subsp. ballota (Desf.) Samp.) - Clavería, Vanessa; De Miguel, Ana Mª (IV Congreso Forestal Español, 2005)
The aims of this study are to characterize the ectomycorrhizal community of a mature and well preserved evergreen oak forest (Quercus ilex L. subsp. ballota (Desf.) Samp.) and to relate the above- and below-ground species diversity. The study area is the Nature Reserve of Monte del Conde, which has been proposed to be included in the Sites for Community Importance (SCI) and for Special Areas of Conservation (SAC) for the European Community. In autumn 2003, in an area of 225 m2, 374 sporocarps belonging to 52 taxa were collected. Clavulina cinerea (Fr.) Schroet., Entoloma rhodopolium (Fr.) Kumm. and Tricholoma scalpturatum (Fr.) Quél. were the dominant species. Belowground, morphological and anatomical analyses of ectomycorrhizal root tips were performed, yielding a total of 41 types. Cenococcum geophilum Fr. and thelephoroid fungi were dominant species on the root system. The preliminary results show that the sporocarps survey does not reflect the real ectomycorrhizal community diversity. Therefore, it is important to sample both sporocarps and root tips to achieve an accurate estimate of the ectomycorrhizal fungal community in forest ecosystems.
The following values have no corresponding Zotero field: periodical: IV Congreso Forestal Español issue: 1992 pub-location: Zaragoza
Keywords: Ectomycorrhizae; ectomycorrhizal fungi; Quercus ilex; sporocarps